Safe sleep crib clinics: Promoting risk reduction strategies for sudden unexpected infant death - Carolyn R. Ahlers-Schmidt; Christy Schunn; Ashley M. Hervey; Maria Torres (PEC Innovation)
Objectives: Safe Sleep Community Baby Showers (CBS) provide group education to reduce risk factors of sudden unexpected infant death (SUID). Based on CBS success, Safe Sleep Crib Clinics were developed to provide individual education. This study assessed Crib Clinic outcomes and differences in Crib Clinics compared to CBSs. Methods: Certified Safe Sleep Instructors facilitated CBSs and/or Crib Clinics in their communities and collected participant data related to safe sleep, tobacco avoidance and breastfeeding. Crib Clinic data was compared pre- to post-test; post-test results were compared between Crib Clinics and CBSs. Results: Crib Clinic attendees exhibited significant increases in intention to have infant follow safe sleep recommendations, avoid secondhand smoke and breastfeed (all p < 0.001). Significant differences between Crib Clinic and CBS participants related to marital status, language, tobacco, education and insurance (all p < 0.01). CBS and Crib Clinic participants differed on items related to sleep environment, breastfeeding and tobacco (all p = 0.05). Conclusions: Overall Crib Clinics appear to be effective in increasing knowledge, intentions and confidence related to safe sleep, tobacco avoidance and breastfeeding. Crib Clinics may offer flexibility (e.g., time, format) that increases accessibility to safe sleep education for families. Innovation: Results suggest the ability to shift education delivery method based on group size was important in both rural and urban settings.